2017
DOI: 10.1007/978-3-319-64027-3_21
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Potential of Combining Functional Near-Infrared Spectroscopy with Different Virtual Reality Displays—Oculus Rift and oCtAVE

Abstract: Ti t l e Tes ti n g t h e p o t e n ti al of c o m bi ni n g fu n c tio n al n e a r-infr a r e d s p e c t r o s c o py wi t h diffe r e n t vir t u al r e ality di s pl ay sO c ul u s Rift a n d oC tAVE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The study showed that anxiety levels were higher in patients who were physically moving during exposure to heights, and the locomotion also improves a sense of presence (Slater et al, 1998 ). Such Cave–like systems provide an opportunity for combining with portable brain imaging devices without obscuring data quality due to the movement or sensor displacement when using HMDs (Landowska et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that anxiety levels were higher in patients who were physically moving during exposure to heights, and the locomotion also improves a sense of presence (Slater et al, 1998 ). Such Cave–like systems provide an opportunity for combining with portable brain imaging devices without obscuring data quality due to the movement or sensor displacement when using HMDs (Landowska et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HMD iVR may induce less ambient light interference with fNIRS signals, as the display screens are normally fully enclosed within the VR goggle. 31 By contrast, CAVE iVR implements motion tracking cameras to track body movements or as a means of interaction with the virtual space. 91 , 92 Such cameras (e.g., time-of-flight depth cameras 93 ) often use infrared light, which represents a source of interference for fNIRS.…”
Section: Discussionmentioning
confidence: 99%
“… 90 CAVE iVR provides a more natural sense of embodiment as users can see their own bodies during the iVR experience. 31 , 95 Its spacious environment can accommodate additional pieces of equipment, such as a driving simulator or a flight cockpit simulator, to offer realistic visual and haptic feedback. Unlike HMDs, which are generally intended for a single user, CAVE VR can simultaneously immerse multiple individuals in the same environment, 92 facilitating fNIRS research that aims at exploring brain coupling among users, as seen in hyperscan setups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features are particularly relevant to research approaches such as neuroergonomics [13], real-life neuroscience [4], and UX/UI studies [14]. At the same time, the fNIRS developers create more devices that are fully mobile, wireless [15], and designed to work with headmounted displays (HMD) [16] or training apps [17]. VR technology has been used in the research and training of attentional skills due to its ability to isolate the subject from external distractions [18].…”
Section: Introductionmentioning
confidence: 99%